Trends in Research in Ephemeroptera and Plecoptera 2001
DOI: 10.1007/978-1-4615-1257-8_26
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic and Bisexual Populations of Ephemerella Notata Eat. in Poland

Abstract: ABSTRACfThe sex ratio (males: females) of final instar nymphs of Ephemerella notata varies from 0.12: 1.00 to 0.92: 1.00 in isolated populations of the Pomeranian Lake District in Poland. These data support the view that facultative parthenogenesis occurs in this species. The incidence of parthenogenesis was inversely related to population density. Parthenogenetic populations were less variable in size (determined by a principal component analysis of a total body-size index) and more synchronous in their devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Obligatory parthenogenesis is known to exist in several mayfly species (Clemens 1922;Froehlich 1969;Gibbs 1977;Bergman and Hilsenhoff 1978;Sweeney and Vannote 1987;Gillies andKnowles 1990), andHumpesch (1980) reported that the rate of hatching among unfertilized eggs was usually greater than 80% in the obligatory parthenogenesis populations. Evidence of geographic parthenogenesis, i.e., unisexual and bisexual populations of the same species existing in the same geographic area, such as Ephoron shigae in this study, has been verified for two ephemerellid mayflies: the eastern North American Eurylophella funeralis (McDunnough) (Sweeney and Vannote 1987) and the east European (e.g., Polish, Czech) Ephemerella notata Eaton (Jazdzewska 1976;Glazaczow 1994Glazaczow , 2001. The hatching success of unfertilized eggs of Eurylophella funeralis was inversely related to the proportion of males in the bisexual populations (Sweeney and Vannote 1987).…”
Section: Origin Of Obligatory Parthenogenesismentioning
confidence: 91%
See 3 more Smart Citations
“…Obligatory parthenogenesis is known to exist in several mayfly species (Clemens 1922;Froehlich 1969;Gibbs 1977;Bergman and Hilsenhoff 1978;Sweeney and Vannote 1987;Gillies andKnowles 1990), andHumpesch (1980) reported that the rate of hatching among unfertilized eggs was usually greater than 80% in the obligatory parthenogenesis populations. Evidence of geographic parthenogenesis, i.e., unisexual and bisexual populations of the same species existing in the same geographic area, such as Ephoron shigae in this study, has been verified for two ephemerellid mayflies: the eastern North American Eurylophella funeralis (McDunnough) (Sweeney and Vannote 1987) and the east European (e.g., Polish, Czech) Ephemerella notata Eaton (Jazdzewska 1976;Glazaczow 1994Glazaczow , 2001. The hatching success of unfertilized eggs of Eurylophella funeralis was inversely related to the proportion of males in the bisexual populations (Sweeney and Vannote 1987).…”
Section: Origin Of Obligatory Parthenogenesismentioning
confidence: 91%
“…Parthenogenesis is found in most animal groups (Suomalainen 1950(Suomalainen , 1962Glesener and Tilman 1978;Suomalainen et al 1987) and has been reported in some mayflies (Degrange 1960;Huff and McCafferty 1974;Gibbs 1977;Mingo 1978;Humpesch 1980;Sweeney and Vannote 1987;Glazaczow 2001, Ball 2001, 2002. However, in most mayflies parthenogenesis is only facultative, and is occasional or accidental (i.e., tychoparthenogenesis), such as in the North American burrowing mayfly Ephoron album (Say) (Britt 1962;cf.…”
Section: Origin Of Obligatory Parthenogenesismentioning
confidence: 92%
See 2 more Smart Citations
“…E. SHIGAE POPULATIONS Parthenogenesis is found in many animal groups (Suomalainen, 1950(Suomalainen, , 1962Glesener & Tilman, 1978;Suomalainen et al, 1987) and has been reported in some mayflies (Degrange, 1960;Huff & McCafferty, 1974;Gibbs, 1977;Mingo, 1978;Humpesch, 1980;Sweeney & Vannote, 1987;Glazaczow, 2001;Ball, 2001Ball, , 2002. However, in the majority of cases, mayfly parthenogenesis is facultative (termed tychoparthenogenesis or occasional or 'accidental' parthenogenesis).…”
Section: Parthenogenetic Ability Of Bisexualmentioning
confidence: 99%